Systemic Adenosine Triphosphate Impairs Neutrophil Chemotaxis and Host Defense in Sepsis - Li, Xiaoou; Kondo, Yutaka; Bao, Yi; Staudenmaier, Laura; Lee, Albert; Zhang, Jingping; Ledderose, Carola; Junger, Wolfgang G (Critical care medicine, 2017)
Sepsis remains an unresolved clinical problem. Therapeutic strategies focusing on inhibition of neutrophils (polymorphonuclear neutrophils) have failed, which indicates that a more detailed understanding of the underlying pathophysiology of sepsis is required. Polymorphonuclear neutrophil activation and chemotaxis require cellular adenosine triphosphate release via pannexin-1 channels that fuel autocrine feedback via purinergic receptors. In the current study, we examined the roles of endogenous and systemic adenosine triphosphate on polymorphonuclear neutrophil activation and host defense in sepsis. Prospective randomized animal investigation and in vitro studies. Preclinical academic research laboratory. Wild-type C57BL/6 mice, pannexin-1 knockout mice, and healthy human subjects used to obtain polymorphonuclear neutrophils for in vitro studies. Wild-type and pannexin-1 knockout mice were treated with suramin or apyrase to block the endogenous or systemic effects of adenosine triphosphate. Mice were subjected to cecal ligation and puncture and polymorphonuclear neutrophil activation (CD11b integrin expression), organ (liver) injury (plasma aspartate aminotransferase), bacterial spread, and survival were monitored. Human polymorphonuclear neutrophils were used to study the effect of systemic adenosine triphosphate and apyrase on chemotaxis. Inhibiting endogenous adenosine triphosphate reduced polymorphonuclear neutrophil activation and organ injury, but increased the spread of bacteria and mortality in sepsis. By contrast, removal of systemic adenosine triphosphate improved bacterial clearance and survival in sepsis by improving polymorphonuclear neutrophil chemotaxis. Systemic adenosine triphosphate impairs polymorphonuclear neutrophil functions by disrupting the endogenous purinergic signaling mechanisms that regulate cell activation and chemotaxis. Removal of systemic adenosine triphosphate improves polymorphonuclear neutrophil function and host defenses, making this a promising new treatment strategy for sepsis.